Community Structure of Water Plants in Laut Tawar Lakes - Hasri, Iwan; Manik, Delian Putra Mandida; Susanti, Zulida; Fahmi, Rizkan (Jurnal Ilmiah Samudra Akuatika, 2022)
This study aims to analyze the community structure of aquatic plants in locations that have floating net cages (KJA) and those that do not have floating net cages in Lake Laut Tawar. The research was conducted from November 2021 to January 2022. The research method used was descriptive analytic consisting of 5 stations, each station was repeated 3 times. Observation stations consist of Mendale and One-one which represent KJA waters. Bebuli, Mepar and Kala Segi representing regions do not have KJA. Based on the results of the study, 3 types of aquatic plants were found, Eichhornia crassipes, Hydrilla verticillata and Salvinia molesta. The highest biomass is found in the KJA area at One one station with a biomass of 5 906.67 g/m2. The uniformity index (H') values ​​range from 0.35-0.69, the E uniformity index ranges from 0-0.48 and the dominance index (D) ranges from 1.37-3.79. Aquatic plants in the KJA area are characterized by higher dissolved solids, nitrate and total phosphate values ​​compared to KJA.